Uji Efektifitas Bakteri Antagonis Untuk Pengendalian Penyakit Layu pada Tanaman Stroberi - SHAH KANIGARA ASADDIARI; GUSTI NNGURAH ALIT SUSANTA WIRYA; I KETUT SIADI; I MADE SUDANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Effectiveness Test of Antagonistic Bacteria to Control Strawberry Wilt Disease Strawberry (Fragaria sp.) Is a herbaceous fruit plant that was first discovered in Chile, USA. Bali Province is one of the provinces that produce strawberries inIndonesia. The development center for strawberry commodity in the Province of Baliis in the Bedugul area, that is in the Village of Pancasari, District of Sukasada andVillage of Candikuning, District of Tabanan. Since 2016, there have been quiteharmful disorders in strawberry plants in Bali due to wilting caused by the fungusFusarium oxysporum. Research on the effectiveness test of antagonistic bacteria tocontrol strawberry wilt disease was conducted in January 2019 to August 2019. Thepurpose of this study was to determine the ability of antagonistic bacteria to controlthe growth of wilt disease in strawberries in vivo. The method used is the isolation ofbacteria and pathogens, application of bacterial and pathogenic isolates, andobservation. The results of this study are that the P3 bacterial isolate is able to controlthe most effective pathogens with a disease percentage of 20 %.